A love of life and the land - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Globalisation is making its mark on our food through more and more products which seem to be more and more the same. At the same time, the market for 'local foods' is growing apace in many countries to the great delight of consumers yearning for...